EXPERT’S VIEW ON THE MIRACLES OF THE QUR’AN IN FIELD OF FAMILY LAW - Sa'bana, Sofi Mubarokah (Prodi Pendidikan Agama Islam STAI Darul Falah, 2024)
This research aims to examine whether the miracles of the previous prophet were different from the miracles of the prophet Muhammad. The miracles of the previous prophets are hissiyah (sensory) miracles that can be captured by the five human senses and are impermanent only until the death of the prophet in question in contrast to the miracles of the Qur’an which were revealed to the prophet Muhammad which are meaningful (rational) because it can be seen from scientific miracles that are rational there is related to human rational thinking. The Al-Qur’an is different from human compositions because the Al-Qur’an is a complement to the previous books. The arrangement of words and sentences when viewed from the aspect of language is more beautiful than any Arabic poetry even the highest poets can not match the language of the Qur’an apart from being viewed from the aspect of language. The Qur’an also explains scientific matters such as the occurrence of the universe, human reproduction, and other scientific matters. The Qur’an also reports about news of the occult, such as future events. This research is included in library research. The sources come from library literature in the form of the Al-Qur'an, books, scriptures, and journals related to the theme discussed.